HUBUNGAN UMUR, PENDIDIKAN, PARITAS, PENYAKIT PENYERTA TERHADAP KEJADIAN ABORTUS DI INSTALASI RAWAT INAP KEBIDANAN RSD KALISAT JEMBER 2014 - Herlidian Putri (Jurnal Kesehatan dr. Soebandi, 2015)
Abortion is the discharge of the fetus before reaching viability. Where the gestation period has not reached the age of 22 weeks and weighs less than 500gr. One type of abortion is incomplete abortion. the number of incomplete abortion patients in RSD Kalisat January-2014 2014. The purpose of this study was to determine the relationship of age, education, parity and accompanying diseases with the occurrence of incomplete abortion in the Inpatient Hospital of Kalisat Jember Hospital in 2014. This study used a retrospective approach. The sample in this study were mothers who had incomplete abortion who were treated in the midwifery room of Kalisat Jember Hospital in 2014 recorded in the medical record with a sample of 107. Analysis using Chi-Square. From the analysis of the relationship of age with incomplete abortion the significance value is 0.004 <0.05, the relationship between education and incomplete abortion is a significance value of 0.000 <0.05, the relationship of parity with incomplete abortion is a significance value of 0,000 <0.05, the relationship of comorbidities with incomplete abortion is of significance 0,000 <0.05, so that there is a relationship between age and incomplete abortion, education with incomplete abortion, parity with incomplete abortion, comorbidities with incomplete abortion in the Inpatient Hospital of Kalisat Jember Hospital in 2014. It is expected that mothers pay attention to the importance of age status, education, parity , comorbidities during pregnancy